21st Century Skills of Junior High School Science Teachers: A Training Needs Assesment - Unsi, Alibai; MENTOK, SAMER G.; SAM, SOLAYHA A. (Advances in Social Sciences Research Journal, 2021)
Classroom teachers need to be familiar with 21st century skills and integrate them throughout the curriculum as these directly impact teaching and learning. This study assessed the 21st century skills of Junior High School Science teachers of Cotabato City Division as a form of training needs assessment for professional development. This study also answered the level of proficiency of the respondents in terms of Learning and Innovation Skills, information, media and technology skills, and career and life skills. This study used descriptive quantitative approach using a questionnaire adapted from framework developed by the Partnership for 21st Century Learning (P21). The analysis and interpretation used descriptive and inferential statistics. The Learning and Innovation Skills got the lowest grand mean, while the information, media and technology got the highest grand mean. There is no statistically significant difference between the mean ratings of the proficiency of the skills of the teachers and the administrators. This study concludes that the Junior High School Science teachers of Cotabato City Division have highly practiced/ applied 21st Century Skills. The means revealed that the respondents are most proficient information, media and technology skills and are less proficient in Learning and Innovation Skills.